Visual Texts, Ceremonial Texts, Texts of Exploration Collected Articles on the Representation of Russian Monarchy - Wortman, Richard (Academic Studies Press, 2014)
Visual Texts, Ceremonial Texts, Texts of Exploration continues the work begun in Russian Monarchy: Representation and Rule, which analyzed the interplay between the symbolic representations of Russian monarchs and the legal and institutional instruments of their rule. The articles in this volume examine the texts that, through various media, revealed the myths and scenarios conveying the goals and ideals the monarchy sought to elevate before the elite of the empire and, later, the public at large.